King-type operators related to squared Szász-Mirakyan basis - HOLHOȘ, Adrian (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
In this paper we study some approximation properties of a sequence of positive linear operators defined by means of the squared Szász-Mirakyan basis and prove that these operators behave better than the classical Szász-Mirakyan operators. Mathematics Subject Classification (2010): 41A36, 41A60.